β-Lactoglobulin gene polymorphism in Indian sheep breeds of different agro-climatic regions - JYOTSANA, BASANTI; KUMAR, RAJIV; KUMARI, RAJNI; MEENA, A S; PRINCE, L L L; PRAKASH, VED; KUMAR, SATISH (The Indian Journal of Animal Sciences, 2014)
Two genetic variants (A and B) and three genotypes (AB, BB and AA) were found in studied sheep breeds. The average frequency of A and B allele was (0.59) and (0.41) respectively. The A allele was more frequent among the studied breeds except Patanwadi and Kendrapada breeds. There was no clear cut predominance of any of the genotype. The Patanwadi, Malpura, Dumba, Kendrapada and Chokla populations were not in Hardy-Weinberg equilibrium. These results suggested the presence of β-LG gene polymorphism and predominance of β-LG A type in majority of the studied breeds. From the above findings it may be concluded that the native sheep breeds depicts variation in β-LG exon II locus. Further, genotype and allele distribution pattern in different breeds may be due to different characteristic of milk of these breeds. The contrasting pattern of variation observed in present study compared to previous study in native sheep breeds also highlight the need for further studies using large number of animals from different geographic regions. The relationship between β-LG genetic variants and traits related to milk and cheese production characteristics in rest of Indian sheep breeds need to be explored.